Systematics of central heavy ion collisions in the 1A GeV regime - Reisdorf, Willibrord; Andronic, A.; Averbeck, R.; Benabderrahmane, Mohamed Lotfi; Hartmann, O. N.; Herrmann, Norbert; Hildenbrand, K. D.; Kang, T. I.; Kim, Y. J.; Kiš, M.; Koczoń, P.; Kress, T.; et al. (Nuclear physics. A, Nuclear and hadronic physics, 2010)
Using the large acceptance apparatus FOPI, we study central collisions in the reactions (energies in A GeV are given in parentheses): 40Ca+40Ca (0.4, 0.6, 0.8, 1.0, 1.5, 1.93), 58Ni+58Ni (0.15, 0.25, 0.4), 96Ru+96Ru (0.4, 1.0, 1.5), 96Zr+96Zr (0.4, 1.0, 1.5), 129Xe+CsI (0.15, 0.25, 0.4), 197Au+197Au (0.09, 0.12, 0.15, 0.25, 0.4, 0.6, 0.8, 1.0, 1.2, 1.5). The observables include cluster multiplicities, longitudinal and transverse rapidity distributions and stopping, and radial flow. The data are compared to earlier data where possible and to transport model simulations.
Gesehen am 12.05.2023